Development of a thermal excitation source used in an active thermographic UAV platform - Deane, Shakeb; Avdelidis, Nicolas P.; Ibarra-Castanedo, Clemente; Williamson, Alex A.; Withers, Stephen; Zolotas, Argyrios; Maldague, Xavier P.; Ahmadi, Mohammad; Pant, Shashank; Genest, Marc; Rabearivelo, Hobivola A.; Tsourdos, Antonios (Taylor & Francis, 2022)
This work aims to address the effectiveness and challenges of using active infrared thermography (IRT) onboard an unmanned aerial vehicle (UAV) platform. The work seeks to assess the performance of small low-powered forms of excitation which are suitable for active thermography and the ability to locate subsurface defects on composites. An excitation source in multiple 250 W lamps is mounted onto a UAV and is solely battery powered with a remote trigger to power cycle them. Multiple experiments address the interference from the UAV whilst performing an active IRT inspection. The optimal distances and time required for a UAV inspection using IRT are calculated. Multiple signal processing techniques are used to analyse the composites which help locate the sub-surface defects. It was observed that a UAV can successfully carry the required sensors and equipment for an Active thermographic NDT inspection which can provide access to difficult areas. Most active thermographic inspection equipment is large, heavy, and expensive. Furthermore, using such equipment for the inspection of complex structures is time-consuming. For example, a cherry picker would be required to inspect the tail of an aircraft. This solution looks to assist engineers in inspecting complex composite structures and could potentially significantly reduce the time and cost of a routine inspection.
Keywords: Active infrared thermography; excitation source; signal processing; UAV; aircraft-grade composites